2015
DOI: 10.1101/lm.038083.115
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glycogen synthase kinase-3β enhances cognitive recovery after stroke: the role of TAK1

Abstract: Memory deficits are common among stroke survivors. Identifying neuroprotective agents that can prevent memory impairment or improve memory recovery is a vital area of research. Glycogen synthase kinase-3β (GSK-3β) is involved in several essential intracellular signaling pathways. Unlike many other kinases, GSK-3β is active only when dephosphorylated and activation promotes inflammation and apoptosis. In contrast, increased phosphorylation leads to reduced GSK-3β (pGSK-3β) activity. GSK-3β inhibition has benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…Increasing evidence from animal studies and human research has indicated a role for the Wnt/β‐catenin pathway in the regulation of cognition in the adult brain . The main biological effect of the canonical Wnt/β‐catenin pathway is to regulate the degradation of β‐catenin through GSK‐3β, and regulating the activity and level of GSK‐3β and β‐catenin has been considered as a potential target for improving cognition . In the present study, protein expression of p‐GSK‐3β increased and p‐β‐catenin expression decreased in the hippocampus and PFC of NAFLD rats, which was consistent with the reported findings from studies conducted in chronic intermittent hypoxia mice .…”
Section: Discussionmentioning
confidence: 46%
“…Increasing evidence from animal studies and human research has indicated a role for the Wnt/β‐catenin pathway in the regulation of cognition in the adult brain . The main biological effect of the canonical Wnt/β‐catenin pathway is to regulate the degradation of β‐catenin through GSK‐3β, and regulating the activity and level of GSK‐3β and β‐catenin has been considered as a potential target for improving cognition . In the present study, protein expression of p‐GSK‐3β increased and p‐β‐catenin expression decreased in the hippocampus and PFC of NAFLD rats, which was consistent with the reported findings from studies conducted in chronic intermittent hypoxia mice .…”
Section: Discussionmentioning
confidence: 46%
“…A better understanding of the role of autophagy in cerebral I/R injury is needed. In this respect, glycogen synthase kinase-3 (GSK-3) not only plays an important role in the neuronal cell death caused by cerebral I/R injury but also regulates autophagic cell death (Venna, Benashski, Chauhan, & McCullough, 2015). Thus inhibition of GSK-3β may provide neuroprotective effects against cerebral I/R-induced injury (Chuang, Wang, & Chiu, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although a few papers reported that inhibition of GSK3β enhanced cognitive recovery after stroke mediated by transforming growth factor‐β‐activated kinase (TAK1), and a COX‐2 inhibitor showed neuroprotection by phosphorylation of Akt and GSK3β (Venna et al, 2015; Ye et al, 2012), our study appears the first demonstration of regenerative benefits of delayed inhibition of the GSK3β signaling after ischemic stroke. Most previous neuroprotective investigations administered neuroprotectants before or acutely after the onset of stroke, which may at least partly explain the difficulties of translating these treatments to clinical settings.…”
Section: Discussionmentioning
confidence: 69%